2015
DOI: 10.1111/dote.12435
|View full text |Cite
|
Sign up to set email alerts
|

Reduced toxicity with three-dimensional conformal radiotherapy or intensity-modulated radiotherapy compared with conventional two-dimensional radiotherapy for esophageal squamous cell carcinoma: a secondary analysis of data from four prospective clinical

Abstract: We conducted a retrospective analysis to assess the toxicity and long-term survival of esophageal squamous cell carcinoma patients treated with three-dimensional conformal radiotherapy (3DCRT) or intensity-modulated radiotherapy (IMRT) versus conventional two-dimensional radiotherapy (2DRT). All data in the present study were based on four prospective clinical trials conducted at our institution from 1996 to 2004 and included 308 esophageal squamous cell carcinoma patients treated with 2DRT or 3DCRT/IMRT. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The five‐year OS in definition radiotherapy for esophageal carcinoma was 42% and 13% with or without diagnostic computed tomography scanning, respectively . Furthermore, a lower toxicity was also observed using 3‐DCRT compared with conventional two‐dimensional radiotherapy …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The five‐year OS in definition radiotherapy for esophageal carcinoma was 42% and 13% with or without diagnostic computed tomography scanning, respectively . Furthermore, a lower toxicity was also observed using 3‐DCRT compared with conventional two‐dimensional radiotherapy …”
Section: Introductionmentioning
confidence: 92%
“…11 Furthermore, a lower toxicity was also observed using 3-DCRT compared with conventional two-dimensional radiotherapy. 12 Previously, we conducted a prospective phase II study to explore the efficacy of late-course sequential boost 3-DCRT alone for esophageal SCC, and the two-year OS of 69% was attained. 13 To our knowledge, there were limited longterm survival data on esophageal SCC using 3-DCRT or intensity-modulated radiotherapy (IMRT) alone.…”
Section: Introductionmentioning
confidence: 99%
“…It had been reported that there was no significant difference in overall survival, failure-free survival, as well as regional failure-free survival, among the IMRT patients (n � 64) and 2D-RT patients (n � 37) for the treatment of cervical esophageal squamous cell carcinoma from 2001 to 2012 [15]. No substantial survival advantages were detected from the use of 3D-CRT/IMRT in a retrospective analysis based on four prospective clinical trials, which assessed the toxicity as well as long-term survival of ESCC patients treated with 3D-CRT or IMRT in comparison with that of 2D-RT [22]. e ambiguous or contradictory results may be due to the lack of data concerning the potential value of IMRT in a dose-escalated radiotherapy setting.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the optimal radiation dose remains to be determined. Finally, three-dimensional conformal radiotherapy (3DCRT) for unresectable EC yields 5-year OS rates of 34-45.6% [10][11][12][13], which is an improvement over the rates reported in the RTOG 85 − 01 and 94 − 05 studies. Moreover, radiotherapy (median dose, 60 Gy) with or without concurrent chemotherapy yields 5-year OS rates of 34.7% and 27.7%, respectively [14].…”
Section: Introductionmentioning
confidence: 88%